Integration between Practice of Strategic Human Resource Management and Organizational Strategy Process: View Points from CEOs and Heads of HR in Sri Lankan firms - Sajeevanie, T.L.; Opatha, H.H.D.N.P.; Dissanayake, K. (Faculty of Graduate Studies, University of Colombo, 2015)
The Practice of Strategic Human Resource Management has become more important to strategic management, largely as a result of its role in providing competitive advantage and the rush to competitiveness. Existing literature reveals that it is critical to address the research issue of why the practice of SH R M should integrate with Organizational Strategy Process. The objective of this study was to fin d out reasons for why the practice of SHRM should integrate with Organizational Strategy Process from the viewpoints of Chief Executive Officers and Heads of Human Resource of Sri Lankan Listed Companies. Qualitative approach was used and the research strategy of this study was descriptive. In order to select the respondents the purposive sampling technique was used. Semi-structured interviews were conducted in order to explore the existing uncovered realities. Heads of HR and CEOs of 20 organizations were interviewed and the data were analyzed through thematic analysis. Initially five themes were identified and later refinement produced four themes. These are original contributions to the Sri Lankan SHRM Literature. The findings of the study help fill the existing knowledge gap and provide some practical implications for professionals on SHRM practices in the Sri Lankan context.
Keywords: Integration between Practice of Strategic Human Resource Management and Organizational Strategy Process View Points from CEOs and Heads of HR in Sri Lankan firms; Integration; Organizational Strategy Process